1994
DOI: 10.1577/1548-8667(1994)006<0349:orisbm>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Oxytetracycline Residue in Striped Bass Muscle

Abstract: Tissue residues were measured in striped bass Morone saxatilis that had been injected intraperitoneally with 50 mg Oxytetracycline (OTQ/kg or had been fed a ration containing 75 mg OTC/kg of fish daily for 10 d. Concentration of OTC in muscle of fish fed medicated feed was below the quantitation limit in 67% of the fish 12 d after treatment and was below the quantitation limit in all fish after 16 d at 23°C. The calculated terminal elimination rate constant (ft) was 0.20/d (range, 0.15-0.37/d), and the half-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Regardless, Kosoff et al (2007) conducted a study to monitor sulfadimethoxine and ormetoprim residues in Nile Tilapia, Summer Flounder, and Walleyes after administering the standard therapeutic dose for 10 d and found that (1) neither component could be detected in samples of the edible portion of Walleyes (muscle plus skin) collected on day 10 posttreatment or thereafter, (2) only one Summer Flounder had a detectable concentration of either component on day 21 or thereafter, and (3) the elimination of Romet-30 by Nile Tilapia was extremely rapid. Similar results have shown that drug residues accrued after administration of the standard treatment regimen deplete very quickly (i.e., within hours to days) from fish tissues, including blood plasma, kidney, and muscle (e.g., Allen 1988;Xu 1994;Zhang and Li 2007;Bowser et al 2009;Gaikowski et al 2010). The withdrawal period for Romet-30 is as long as 42 d, depending on the use pattern.…”
Section: Myth I: Hatchery Fish Are "Festooned" With Drug Residuessupporting
confidence: 54%
“…Regardless, Kosoff et al (2007) conducted a study to monitor sulfadimethoxine and ormetoprim residues in Nile Tilapia, Summer Flounder, and Walleyes after administering the standard therapeutic dose for 10 d and found that (1) neither component could be detected in samples of the edible portion of Walleyes (muscle plus skin) collected on day 10 posttreatment or thereafter, (2) only one Summer Flounder had a detectable concentration of either component on day 21 or thereafter, and (3) the elimination of Romet-30 by Nile Tilapia was extremely rapid. Similar results have shown that drug residues accrued after administration of the standard treatment regimen deplete very quickly (i.e., within hours to days) from fish tissues, including blood plasma, kidney, and muscle (e.g., Allen 1988;Xu 1994;Zhang and Li 2007;Bowser et al 2009;Gaikowski et al 2010). The withdrawal period for Romet-30 is as long as 42 d, depending on the use pattern.…”
Section: Myth I: Hatchery Fish Are "Festooned" With Drug Residuessupporting
confidence: 54%
“…The elimination half‐life of OTC in E. sinensis was longer than that in fish (Xu & Rogers 1995; Namdari, Abedini & Law 1999; Zhang & Li 2007). Similarly, the elimination half‐lives of OTC in E. sinensis were longer than the corresponding values in M. rosenbergii and Penaeus chinensis (Wang, Lin, Xue & Khalid 2004a; Poapolathep et al.…”
Section: Discussionmentioning
confidence: 92%
“…After withdrawing OTC in feed, the residues in the muscles were decreased to 37, 10 and 3–7 ng g −1 on 3rd, 7th and 14th days. Xu and Rogers (1994) recommended that by raising fish for 16–24 days at a water temperature of 23°C, OTC could be eliminated from fish muscle. Rigos, Alexis, Andriopoulou and Nengas (2002) showed that OTC is eliminated faster from fish tissue when fish are raised at higher water temperature.…”
Section: Discussionmentioning
confidence: 99%